ANTHROPOCENTRIC DIMENSIONS OF UKRAINIAN CULTURE (IN THE CONTEXT OF THE ARCHETYPE OF THE WISE OLD MAN) - Z. O. Yankovska; L. V. Sorochuk (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. Philosophy of culture is an extremely multifaceted field, which includes the anthropological segment as well. In particular, we can talk about the role of man (personality) in cultural progress in a particular period of development of the society. To some extent, this problem may also apply to the theory of archetypes, which is rapidly developing today, being used not only in philosophy but also in other fields, deeply penetrated into the methodology of humanities knowledge. Therefore, we used interdisciplinary tools for this study. The purpose of this work is to study the influence of personality on the development of Ukrainian culture in a global, comprehensive dimension, based on the experience and works of famous figures that carried out cultural activities in a certain historical period. In this case, we can appeal to the archetype of the Wise Old Man, which contains a set of permanent features (ordinary and transcendent) that connect its projections with both the "foretype" and at the same time the "accumulation" of experience. Theoretical basis. Based on the work of famous researchers in the field of philosophy, anthropology, analytical psychology, ethnophilosophy (C. Jung, Z. Freud, M. Scheler, F. Nietzsche, F. Schelling, W. Eco, G. Gachev, A. Bolshakova, L. Koshetarova, M. Eliade, O. Kyryliuk, S. Krymsky, V. Lychkovakh, T. Shestopalova, M. Nesteleev, Z. Bosyk, etc.), the authors note the insufficient elaboration of the topic regarding the distinction of anthropological (including anthropocentric) dimensions of different cultural periods of Ukraine in chronological order. Originality. The authors of the article prove that the continuity of the accumulation of anthropocentric features in individuals gives them transcendence, elevate to the archetype of the Wise Old Man, which can be perceived as a universal process against the ethnic development background. Conclusions. As a result of the study, we can say that the role of individual key figures in the development of national culture is quite noticeable. This can be traced both at the local level and at the national level, when we should talk about individuals who in a certain period of development of society and culture were leading and became a kind of embodiment of universal experience accumulated in an individual with a certain identity, which is the "personality" required in "that place" and "that time". For this reason, we turn to the archetype of the Wise Old Man as an "invariant", a "conductor", which reflects the most realized and individualized personality in a particular chronotope.